Catheter-related bloodstream infection - Pipatsamut, Piched; Chamradpan, Treechda (Journal of the Nephrology Society of Thailand, 2022)
Catheter-related blood stream infections (CRBSI) are among the common complications encountered in patients with end stage renal disease (ESRD) who received hemodialysis with central venous catheters. CRBSI can cause disability, increased morbidity and mortality, longer length of hospital stays as well as increased health care costs in these patients. Here in, we reviewed with regard to definition, the mechanism of infection, the etiology and organisms involved, the types of infections, the treatment of CRBSI, and the preventive measures. As of today, previous studies demonstrate many preventive measures e.g., use of antibiotic locks, shower safety, nares decolonization and using chlorhexidine caps. The aim of all these preventive measures is to decrease the rate of infection with proper efficiency, cost-effectiveness and convenience without increasing in the incidence of antibiotic resistance nor decreasing in duration of use of catheters. All preventive measure should be applied to everyday practice in hemodialysis unit.